Thinking inside the box : adventures with crosswords and the puzzling people who can't live without them - Raphel, Adrienne (Penguin Press, 2020)
"The crossword is a feature of the modern world, inspiring daily devotion and obsession from not just everyday citizens looking to pass the time but icons of American life, such as Bill Clinton, Yo-Yo Ma, and Martha Stewart. It was invented in 1913, almost by accident, when a newspaper editor at the New York World was casting around for something to fill some empty column space for that year's Christmas edition. Practically overnight, it became a roaring commercial success, and ever since then has been an essential ingredient of any newspaper worth its salt. Indeed, paradoxically, its popularity has never been greater, even as the world of media and newspapers, its natural habitat, has undergone a perilous digital transformation. But why, exactly, are its satisfactions so sweet that over the decades has it become a fixture of breakfast tables, nightstands, and commutes, and even given rise to competitive crossword tournaments? Blending first-person reporting from the world of crosswords with a delightful telling of its rich literary history, Adrienne Raphel dives into the secrets of this classic pastime. At the annual American Crossword Puzzle Tournament, she rubs shoulders with elite solvers of the world, doing her level best to hold her own; aboard a crossword themed cruise, she picks the brains of the enthusiasts whose idea of a good time is a week on the high seas with nothing but crosswords to do; and, visiting the home and office of Will Shortz, New York Times crossword puzzle editor and NPR's official 'Puzzlemaster,' she goes behind the scenes to see for herself how the world's gold standard of puzzles is made"--